The colors of natural scenes benefit dichromats - Pastilha, Ruben Carpinteiro (2019)
Dichromacy impairs color vision and impoverishes the discrimination of surface colors in natural scenes. Computational estimates based on hyperspectral imaging data from natural scenes suggest that dichromats can discriminate only about 10% of the colors discriminated by normal trichromats. These estimates, however, assume that the colors are equally frequent. Yet, pairs of colors confused by dichromats may be rare and thus have small impact on overall perceived chromatic diversity. This study estimated, empirically, how much dichromats are disadvantaged in discriminating surface colors drawn from natural scenes. The stimulus for the experiment was a scene made of real three-dimensional objects painted with matte white paint and illuminated by a spectrally tunable light source. In each trial the observers saw the scene illuminated by two spectra in two successive time intervals and had to indicate whether the colors perceived in the objects in the two intervals were the same or different. The spectra were drawn randomly from hyperspectral data of natural scenes and therefore represented natural spectral statistics. Four normal trichromats and four dichromats carried out the experiment. It was found that the number of pairs that could be discriminated by dichromats was almost 70% of those discriminated by normal trichromats, a proportion much higher than anticipated from estimates of discernible colors. Moreover, data from model simulations show that normal trichromats and dichromats use lightness differences for discrimination in about 40% and 50% of the discriminable pairs, respectively. Together these results suggest that the color distributions of natural scenes benefit the color vision of dichromats.